Land Issues in Poverty Reduction Strategies and the Development Agenda: Philippines - Gilberto M. Llanto; Marife M. Ballesteros (Philippine Institute for Development Studies (PIDS), 2003)
The paper discusses critical land issues in the Philippines and assesses the integration of those issues in the national development agenda and poverty reduction strategies. It covers issues related to agriculture, forest and urban lands, land administration and management and government programs on agrarian reform and housing development. Severe problems affect the land markets in the country and these arise from unclear and inconsistent land laws, policies and inadequacies in land administration and management. These inefficiencies have to be addressed to have sustained growth and alleviate poverty. Land reform is the critical policy intervention in the agrarian and urban sector. The implementation of the program, however, has been hampered by a number of land use and ownership issues. It has been noted that land redistribution per se is not sufficient to motivate rural development. Sustainable management of natural resources and efficient infrastructure development has to be undertaken to make agriculture viable and create balanced regional development. Some priority measures that need to be undertaken are as follows: (1) Completion of cadastral survey of the entire country and use of cadastral maps as bases for land use and physical planning, tax mapping, and other activities; (2) Identification and delineation of forestlands that can be used for agricultural expansion/activities and non-agricultural activities; (3) Identification and delineation of existing and potential agricultural production areas and the provision of necessary support infrastructure, facilities and services;(4) Mapping protected areas and establishing a database for such areas; and (5) Identification and protection of priority infrastructure rights-of-way.
Keywords: 330; property rights; agrarian reform; land administration; poverty reduction; housing and urban development; Bodenmarkt; Bodenpolitik; Institutionenökonomik; Armut; Armutsbekämpfung; Agrarreform; Philippinen